Extending the Evolutionary Synthesis Darwin's Legacy Redesigned - Lange, Axel (Taylor & Francis Group, 2023)
The theories of evolution are themselves evolving with new findings and changes in the fundamental underlying concepts. It is true that today's theory, which goes back to Darwin, is persistently successful. But there remain many unanswered questions
Description based on publisher supplied metadata and other sources
Keywords: Evolution (Biology)